Sustainable Strategies for Broiler Waste Management: Insights from Stakeholder Prioritization in Thailand - Bandara, Senaka (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Thailand’s significant contribution to the global chicken meat industry demands the adoption of sustainable broiler waste management practices, particularly as countries worldwide strive to implement strict policies aimed at reducing emissions from agricultural products. This study employed the Analytic Hierarchy Process (AHP) to analyze diverse stakeholder perceptions regarding the adoption of these practices, utilizing a multi-criteria decision-making approach. Experts prioritized environmental concerns (0.4386), emphasizing sustainability, while farm owners prioritized economic factors (0.5987), reflecting profit-driven motives. Subcriteria analysis highlighted the significance of financial aspects, with “Capital cost” attaining the highest weight (26.05%), followed by environmental concerns like “Climate change” (11.05%). Technical feasibility and societal considerations received moderate prioritization. Stakeholder preferences for waste management methods further highlighted divergent perspectives, with experts favoring gasification for its environmental benefits, while owners prioritized land application for its cost-effectiveness. Composting emerged as a balanced choice. These findings emphasize the importance of considering diverse criteria in waste management decision-making, highlighting the need for comprehensive approaches to ensure sustainability in Thailand's broiler waste management practices.